Art and Techniques for Oral Presentation in Distance Education - Rashid, AQM Bazlur (Journal of Agriculture & Rural Development, 2008)
Human being is only the unique verbal monster in the nature having worldwide communicative power capable of conveying his thought or deliberation and/ or message/information outside his head to others through different ways among which the vocabulary speech is significantly more important and effective. The instructional approach through multi-mediated method of distance education requires persuasible and emanating resourceful speaker with vocabulary and other necessary art and techniques. Relevant qualifications of the speaker along with some important points of consideration such as determination to succeed, control over nervousness, contemporary knowledge, vocabulary efficiency, choice of words and other techniques for opening presenting and closing a speech etc. have been described. Various art and manner including smiling face with emanating attitude, language and style etc. along with avoidable distracting habits of the presenter have also been elucidated in detail. Key words: Art and technique, oral presentation, distance education.